Positron probing of phosphorus-vacancy complexes in silicon irradiated with 15 MeV protons. (May 2015) - Arutyunov, N; Emtsev, V; Krause-Rehberg, R; Elsayed, M; Kessler, C; Kozlovski, V; Oganesyan, G
Abstract: Defects in phosphorus-doped silicon samples of floating-zone material, n -FZ-Si(P), produced under irradiation with 15 MeV protons at room temperature are studied by positron annihilation lifetime spectroscopy over the temperature range of ∼ 30 K - 300 K and by low- temperature Hall effect measurements. After annealing of E -centersand divacancies, we detected for the first time high concentrations of positron traps which had not been observed earlier. These defects are isochronally annealed over the temperature interval of ∼ 320 °C - 700 °C; they manifest themselves as electrically neutral deep donor centersin the material of n -type. A long-lived component of the positron lifetime, τ2 ( I 2 < 60%) ∼ 280 ps, attributed to these centers, suggests a relaxed configuration involving two vacancies. The enthalpy and entropy of annealing of these centersare E a ∼ 1.05(0.21) eV and Δ S m ≈ 3.1(0.6) k B, respectively. It is argued that the microstructure of the defect consists of two vacancies, VV, and one atom of phosphorus, P. The split configuration of the VPV complex is shortly discussed.